Potential Social and Economic Repercussions of The Transhumanist Revolution - M.S.P.S., Ana; Horta, Catarina; Landim, Ema; Caetano, Maria; Frazão, I.C.G.V. (BBDS - Black Book: Drawing and Sketching, 2021)
Our project consists of a visual novel game called Not Today, centered around the topic of transhumanism and its possible repercussions in our society. Transhumanism is a cultural and intellectual movement that advocates the creation of mechanisms to enhance various parameters of human life and revolutionise the notion of what it means to be human. It presents very attractive solutions, a long and promising future for mankind, and the potential achievement of the dream of eternal life. However, from a social and ethical point of view, we encounter many obstacles to the soundness of the proposed solutions. Through our project, we managed to create an interactive experience that aims to expose a utopian scenario in which our society was divided into two distinct factions: the transhumans (the rich and powerful) and the humans (the lowlifes). This split in society occurred with the arrival of the transhumanist revolution, which widened the already existing social inequalities. Not Today takes the player on a journey into this new society, through the eyes of a member of the poor class that decides to rebel against the system. During his cross-country journey to seek freedom, the player will learn more about transhumanism and its possible harmful effects and will go through various challenges, gradually getting to know this society in depth. The ultimate goal is above all to surprise the players and take them through an immersive experience to get to know the darker side of this movement, to foster debate on the subject and generate more sensitivity to the issue.